Schwannoma of the mental nerve: Case report and literature review - LÜ Pengxiang; GONG Yanling; WANG Hengkun; WANG Renxin; ZHENG Xiaotao (Kouqiang hemian waike zazhi)
Schwannoma of the head and neck region is relatively common, however, schwannoma arising from the mental nerve is a rare occurrence. We hereby describe a case of schwannoma involving the mental nerve and review the literature.